Retraction: Hellinen et al. Retinal Pigment Epithelial Cell Line with Fast Differentiation and Improved Barrier Properties. Pharmaceutics 2019, 11, 412 - Laura Hellinen; Lea Pirskanen; Unni Tengvall-Unadike; Arto Urtti; Mika Reinisalo (MDPI AG, 2022)
The published article [...]